2022
DOI: 10.3389/fcell.2022.898088
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia is Associated With Reduced ISG15 Levels Impairing Extravillous Trophoblast Invasion

Abstract: Among several interleukin (IL)-6 family members, only IL-6 and IL-11 require a gp130 protein homodimer for intracellular signaling due to lack of intracellular signaling domain in the IL-6 receptor (IL-6R) and IL-11R. We previously reported enhanced decidual IL-6 and IL-11 levels at the maternal-fetal interface with significantly higher peri-membranous IL-6 immunostaining in adjacent interstitial trophoblasts in preeclampsia (PE) vs. gestational age (GA)-matched controls. This led us to hypothesize that compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Our transcriptome analysis also shows that interferon-related signaling pathways, including ISGylation, are upregulated in TUA medium relative to TA medium. Pertinently, reduction in levels of ISG15 that is required for ISGylation is associated with preeclampsia and knockdown of ISG15 expression impairs invasion of HTR8/SVneo cells in culture 26 . ISGylation has also been reported to modulate the stability of multiple proteins, including YAP, P63, and HIF1α, which play a critical role in trophoblast development 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Our transcriptome analysis also shows that interferon-related signaling pathways, including ISGylation, are upregulated in TUA medium relative to TA medium. Pertinently, reduction in levels of ISG15 that is required for ISGylation is associated with preeclampsia and knockdown of ISG15 expression impairs invasion of HTR8/SVneo cells in culture 26 . ISGylation has also been reported to modulate the stability of multiple proteins, including YAP, P63, and HIF1α, which play a critical role in trophoblast development 27 .…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, FOXP3 [446], TIMP4 [447], OAS3 [448], SOCS1 [128], CD74 [129], PLK1 [449], TGFB1 [450], RAPGEF1 [451], SERPINH1 [452], ATF5 [66], GATA6 [133], IGF2BP1 [453], IRX3 [454], FOXC2 [455], SNHG17 [456], TAF1C [457], HHIP (hedgehog interacting protein) [458], POMC (proopiomelanocortin) [459], DOK5 [76], COL1A1 [460], POSTN (periostin) [461], SOD3 [462], ADAMTS13 [463], FABP5 [464], MAPK11 [465], KCTD15 [83], HSPG2 [466], MST1 [467], MGAT2 [468], LGR5 [469], SPINK1 [470], CYP19A1 [471], PLAC8 [90], CD36 [472], AQP5 [473], GIPR (gastric inhibitory polypeptide receptor) [474], ARG1 [475], SORL1 [476], CD4 [477], F11R [478], LEPR (leptin receptor) [479], CDH13 [480], AR (androgen receptor) [481], FOXO1 [102], MALT1 [482], PAM (peptidylglycine alpha-amidating monooxygenase) [483], B2M [484], TCF4 [485], CAV2 [486], HSBP1 [487], COLEC12 [488], ADRA2A [489], SLC38A4 [490], TM6SF2 [491], GLP2R [111], KLB (klotho beta) [492], NFAT5 [493], PON2 [494], ZMAT3 [495], DST (dystonin) [426], MGST3 [496], COQ2 [118], EPHX2 [497], C2 [181] and FAM3C [120] are altered expression in type 2 diabetes mellitus. Previous studies have shown that DRD4 [498], TIMP4 [499], SOCS1 [500], CD74 [501], TGFB1 [502], ACTG2 [503], ISG15 [504], HOXC8 [505], SNHG17 [506], IL1RL1 […”
Section: Discussionmentioning
confidence: 99%
“…Since it has been proven that oxidative stress is a characteristic feature o preeclamptic pregnancies [26], we evaluated the effect of oxidative stress on HTRA expression in HTR8/SVneo and BeWo cell lines; two placental cell lines were used a models of extravillous [27][28][29] and villous cytotrophoblast [30][31][32], respectively Moreover, the BeWo cell line can be used as a syncytiotrophoblast model whe syncytialization is induced by forskolin [25]. As shown in Figure 2, HTRA1 expressio was significantly increased under oxidative stress in both BeWo and HTR8/SVneo cell (Figure 2A).…”
Section: Oxidative Stress Increased Htra1 Protein Expression In Bewo ...mentioning
confidence: 99%